Análisis de las características silvopastoriles como fuentes de alimentación eficientes en la ganadería, en Ecuador - Burbano Mendoza, Milena Elizabeth (2022)
The collection of information refers to: Analysis of silvopastoral characteristics as efficient feed sources in livestock, in Ecuador. The silvopastoral system requires that resources be managed in such a way that trees and shrubs are preserved over time and are also used as fodder. In addition, they can contribute significantly to the maintenance of continuous vegetation cover. Linked to this, it can protect the soil, can increase fertility in the medium term, as well as provide verifiable benefits in terms of animal production. It is necessary to indicate that the silvopastoral system is characterized by the interaction of grasslands, trees, or shrubs (woody or fruit-bearing) and cattle so that each one of the products they offer is used and that it serves so that the cattle increase their production both in milk as in meat; The benefits provided by silvopastoral systems consist of diversifying products (milk, meat, wood, poles and firewood), providing shade, improving the diet of animals, reducing the use of chemical and concentrated fertilizers, therefore taking advantage of what the farm and in turn maintain the environment free of prejudice and allow ranchers to save or invest less in production costs, taking advantage of available resources in a sustainable manner, where ruminants have higher productivity.